Effects of a Nonviolent Communication-Based Empathy Education Program for Nursing Students: A Quasi-Experimental Pilot Study - Jieun Sung; Youngran Kweon (MDPI AG, 2022)
This study aimed to develop and examine the effects of a nonviolent communication empathy education program, based on a cyclical empathy model of self-esteem, empathic ability, interpersonal relationships, and communication competency for nursing students. Participants were first-grade nursing students from two different colleges in Korea. There were 62 participants: 32 and 30 in the experimental and control groups, respectively. The experimental group received six sessions of 120 min each. The sessions were based on nonviolent communication content and utilized teaching methods such as lectures, presentations, personal activities, group activities, role plays, assignments, and reflective journals. The data were analyzed with percentage, χ²-test, Fisher's Exact test, and a two-group independent means t-test using the SPSS 24.0 program. There were significant increases in self-esteem (t = 4.06, p < 0.001), empathic ability (t = 5.22, p < 0.001), interpersonal relationships (t = 5.14, p < 0.001), and communication competency (t = 5.27, p < 0.001) in the experimental group compared to the control group. Therefore, a nonviolent communication empathy education program based on the cyclical empathy model is expected to be useful for the humanities and social education in a nursing curriculum. Furthermore, it can improve human nursing competency based on multidimensional empathy in clinical settings.